Evaluation of the ADOS Revised Algorithm: The Applicability in 558 Dutch Children and Adolescents - de Bildt, Annelies (Springer US, 2009)
The revised ADOS algorithms, proposed by Gotham et al. (J Autism Dev Disord 37:613–627, 2007), were investigated in an independent sample of 558 Dutch children (modules 1, 2 and 3). The revised algorithms lead to better balanced sensitivity and specificity for modules 2 and 3, without losing efficiency of the classification. Including the restricted repetitive behaviour domain in the algorithm contributes to a clinical ASD classification in modules 2 and 3. For module 1, the results indicate less improvement, probably due to the low-functioning population. In most groups, the advantages of the revised algorithms are achieved without losing the strength of the original algorithm.